Effect of carbohydrate substrate availability on ratings of perceived exertion during prolonged running - Kang, J.; Utter, A.; Nieman, D.; Warren, B. (Medicine & Science in Sports & Exercise, 1997)
The effect of carbohydrate substrate availability on ratings of perceived exertion during prolonged sub-maximal running was evaluated. Marathon runners (N = 30) were assigned to either a placebo (control) or carbohydrate (CHO) feeding group. The experimental trial consisted of 2.5 hr of treadmill running at 75-80% VO2max. The CHO group ingested a 6% glucose solution at the rate of approximately 60 gm/hr. The placebo group consumed an equal amount of artificially flavored water every 15 min. Measurements were taken every 20 min throughout the task. Perceived exertion did not differ between the groups in the first hour but from then on was lower in the CHO group. CHO oxidation was higher in the CHO group at 140-150 min into the exercise. Blood glucose was higher immediately after the exercise in the CHO group. It was concluded that CHO feeding reduces the perception of exertion in the latter stages of prolonged sub-maximal running tasks. Implication. CHO loading and in-task replenishment affects the perception of exertion in the latter stages of long-duration tasks. Thus, for long training sessions as well as long competitive tasks it is a factor which must be considered. Although this study's task was limited to running, until evidence to the contrary is produced, it should also be considered for games such as soccer and Australian Rules football which normally last for periods well in excess of two hours.